2021
DOI: 10.3390/ijerph18147498
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent in Nature Is Associated with Increased Pro-Environmental Attitudes and Behaviors

Abstract: Urbanization, screen dependency, and the changing nature of childhood and parenting have led to increased time indoors, creating physical and emotional distancing from nature and time spent in natural environments. Substantial evidence from observational and intervention studies indicates that overall time spent in nature leads to increased perceived value for connectedness to nature and, subsequently, greater pro-environmental attitudes and behaviors (PEAB). This narrative review of the recent literature eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 120 publications
(139 reference statements)
5
70
0
2
Order By: Relevance
“…37 151 152 Some studies report that a felt affinity for nature is associated with greater levels of eudemonic and hedonic wellbeing 153 154 and pro-environmental behavior. 155 156 Positive self-concept is purported to mediate reports of a so-called ‘warm glow’ following engagement in pro-environmental behavior 157 (i.e. because a person feels it is the right thing to do or they are fulfilling a personal interest).…”
Section: Discussionmentioning
confidence: 99%
“…37 151 152 Some studies report that a felt affinity for nature is associated with greater levels of eudemonic and hedonic wellbeing 153 154 and pro-environmental behavior. 155 156 Positive self-concept is purported to mediate reports of a so-called ‘warm glow’ following engagement in pro-environmental behavior 157 (i.e. because a person feels it is the right thing to do or they are fulfilling a personal interest).…”
Section: Discussionmentioning
confidence: 99%
“…Einen Schritt Richtung "Frieden mit der Natur" zeigt das narrative Review von DeVille et al [21]. Die Ergebnisse der ausgewerteten Interventions-und Beobachtungsstudien zeigen, dass unabhängig von der Qualität der Umweltbedingungen in der Natur verbrachte Zeit sowohl die Wertschätzung gegenüber und die gefühlte Verbundenheit mit der Natur erhöht als auch das Verhalten und die eigene Einstellung umweltfreundlicher werden lässt.…”
Section: Ab In Die Naturunclassified
“…Moreover, studies revealed that there is a significant decrease in people's direct contact with nature (Soga et al 2018;Soga and Gaston 2016). Several causes have been suggested for this rising alienation from nature, including increased urbanization rates, increased use of modern technology for entertainment, changing nature of children and parenting and the view of neighboring natural regions as unsafe (Tandon et al 2012;Soga et al 2018;Deville et al 2021) which resulted in more time spent indoors, producing a physical and emotional disconnection from nature and time spent in natural areas. The lack of experiences in nature may have negative consequences for people's pro-environmentalism (i.e., their pro-EA and pro-EB) (Soga and Gaston 2016;Crowe, 2013;Rosa et al 2018), which could lead to detrimental consequences for the environment (Evans 2019).…”
Section: Environmental Behaviormentioning
confidence: 99%